2008
DOI: 10.1080/00016480801958311
|View full text |Cite
|
Sign up to set email alerts
|

Spindle cell carcinoma as a locally recurrent malignancy after surgery for early lingual squamous cell carcinoma

Abstract: Spindle cell carcinoma (SpCC) of the tongue is a relatively rare malignancy. We treated a patient with metachronous early squamous cell carcinoma (SCC) in both margins of the tongue (right side first followed by left side). Eight years after treatment for the first SCC by surgery and radiotherapy, the second SCC occurred in the contralateral margin of the tongue. Surgical resection was performed for the second SCC, with local recurrence 8 months later associated with pathological change from SCC to SpCC. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…1 There is no definition of an exophytic tumor in the literature, and this can be both a clinical and a pathologic diagnosis. Iguchi et al 10 divided these further, associating endophytic tumors with a higher rate of nodal metastasis and worse survival. 10 We found no difference in survival based on the presence of an exophytic tumor in this study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…1 There is no definition of an exophytic tumor in the literature, and this can be both a clinical and a pathologic diagnosis. Iguchi et al 10 divided these further, associating endophytic tumors with a higher rate of nodal metastasis and worse survival. 10 We found no difference in survival based on the presence of an exophytic tumor in this study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…CK-pan and vimentin were positive and EMA and a-SMA were negative in our patient, based on which spindle cell carcinoma was diagnosed. Iguchi et al [9] reported a case in which SPCC developed as a recurrent tumour following surgery for SCC, suggesting a relationship with radiotherapy. In our patient, radiotherapy and chemotherapy were performed before development of SPCC and these therapies may have promoted an anaplastic change from SCC to SPCC.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, atypical spindle cell proliferation was continuous from the well-differentiated squamous cell carcinoma component. Since only spindle cells may be present in a small biopsied tissue specimen, differentiation from non-epithelial tumours such as fibrosarcoma, synovial sarcoma, leiomyosarcoma, and malignant fibrous histiocytoma is necessary [2,9]. Because the incidence of sarcoma in the oral cavity is generally low, SPCC should also be suspected when only spindle cells are present, and re-investigation by sampling of a relatively large specimen is important.…”
Section: Discussionmentioning
confidence: 99%
“…SpCC has a higher possibility of metastasis compared with classic SqCC. Some risk factors have been reported with SpCC, including male gender, advanced age (over 70 years old), and tobacco and alcohol exposure [5,6]. Prognosis of SpCC has been related to age, tumor location, depth of invasion, growth pattern, history of radiotherapy, vascular invasion, and AJCC tumor staging [1,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Often found as polypoidal, pedunculated, or ulcerated tumors over the head and neck region, SpCC has various symptoms depending on the occurring sites, and the location may alter prognosis [3,4]. Reported risk factors include male gender, advanced age, and tobacco and alcohol exposure [5,6]. Prognosis of SpCC has been related to age, tumor location, depth of invasion, growth pattern, history of radiotherapy, vascular invasion, and American Joint Committee on Cancer (AJCC) tumor staging [1,7,8].…”
Section: Introductionmentioning
confidence: 99%